Maple : 100 sweet and savory recipes featuring pure maple syrup - Webster, Katie (Quirk Books, 2015)
Collects sweet and savory recipes that feature maple syrup, for everything from barbecue sauce to classic cocktails to delectable desserts, with tips on storage, substitution, and do-it-yourself syrup making.